c - Erskine, Kathryn (New York : Philomel Books, 2010)
Ten-year-old Caitlin, who has Asperger's Syndrome, struggles to understand emotions, show empathy, and make friends at school, while at home she seeks closure by working on a project with her father.
A Junior Library Guild selection
2010 National Book Award for Young People's Literature.
Keywords: Family life -- Virginia -- Juvenile fiction; Asperger's syndrome -- Fiction; Empathy -- Fiction; Schools -- Fiction; Death -- Fiction; School shootings -- Fiction; Family life -- Virginia -- Fiction; Virginia -- Fiction; Realistic fiction; Asperger's syndrome -- Juvenile fiction; Empathy -- Juvenile fiction; Schools -- Juvenile fiction; Death -- Juvenile fiction; School shootings -- Juvenile fiction; Families -- Virginia -- Juvenile fiction; Virginia -- Juvenile fiction; Ten-year-old girls -- Fiction; Making friends -- Fiction